The spatial-temporal transfer of scientometrics research topics based on citation analysis - Hou, Jianhua; Yang, Xiucai (Malaysian Journal of Library and Information Science, 2018)
In this study, the spatial-temporal transfer of research topics in the field of scientometrics was analysed through citation analysis and information visualization tools such as CiteSpace and Google Fusion Tables software. We collected 12,839 articles, including 214,748 references, about citation analysis in Science Citation Index-Expanded (SCI-E) and Social Science Citation Index (SSCI) databases for the period of 1971 to July 2016 as the data source. We obtained the following findings: The transfer of central research topics in the field of scientometrics is accelerating. There have been three milestones: the middle of the 1990s, 2005, and 2010. The number of central research topics has also changed from one between 1971 and 1993 to two after 1994 and three after 2008. At the same time, the geographical centres of scientometrics research showed a general shift from the US and Britain to Italy, the Netherlands, Belgium, Spain, and China. At present, the countries that are centres of research include the Netherlands, US, Belgium, China, Spain, and Italy. There is a close positive correlation between the transfer of the central research topic and the transformation of the country to a centre of research. The countries acting as centres of research enjoy not only a high output of literature, but also a great academic influence. Both the theoretical and practical implications of the results are discussed.